Platynosomum fastosum (Digenea: Dicrocoeliidae) infection in a domestic cat in northeastern Brazil: high fluke burden and associated lesions Infecção por Platynosomum fastosum (Digenea: Dicrocoeliidae) em gato doméstico no nordeste do Brasil: alta carga parasitária e lesões associadas doi:10.12662/2317-3076jhbs.v4i3.775.p198-202.2016 - Braga, Roberta da Rocha; Zanchi, Djan; Oliveira, John Allyson Andrade; Teixeira, André Costa; Cavalcanti, Luciano Pamplona de Góes (Journal of Health & Biological Sciences, 2016)
Introduction: Platynosomum fastosum is a dicrocoeliid fluke that infects birds and mammals, especially wild and domestic cats. Case report: A middle-aged male domestic cat was euthanized and examined. Its clinical features had included apathy, emaciation, hepatomegaly and mild jaundice on the mucosae. At necropsy, we noticed enlarged liver and dilated gallbladder. After opening the gallbladder lengthwise, multiple whitish flattened ellipsoidal structures were observed and identified as P. fastosum. The larger parasites were found in gallbladder, with significant different size from cystic duct and intrahepatic biliary ducts (p<0.05). Histopathological analysis revealed fluke-induced suppurative cholecystitis and chronic cholangitis. Precursor lesions of cholangiocarcinoma were reported. Conclusion: This report was part of the first prevalence survey of P.fastosum in municipality of Maracanaú, state of Ceará, northeastern Brazil.